Effect of Drug Therapy and Risk Involved in Coronary Vascular Disease in Type 2 Diabetes Mellitus - A Case Study - Bajracharya, Omi; Rao, B.S.; Khan, G.M (Kathmandu University Journal of Science Engineering and Technology, 2005)
Type 2 Diabetes Mellitus (T2DM) is one of the chronic diseases in the world. According to World Health Organization (WHO) approximately 171 million people worldwide currently on diabetic and that type 2 diabetes accounts to about 90%. This study presents Oral hypoglycemic agent (OHA) prescription pattern by the physicians among Out patients of two hospital and risk involved in coronary vascular disease (CVD). 160 patients previously diagnosed with T2DM were included in the study, which involves review of available documents, interviewing the patients, their sex, age, smoking habit, family history, Body mass index (BMI), lifestyle, associated disease, Cardiac complication, total no of drugs used, no of drugs prescribed and lastly risk involved in development of the CVD in T2DM. 55% male and 45% female were assessed and subjects above 50 years were found susceptible to Hyperglycemia. Smoking status were- present smokers were 19.4 %, ex-smokers were 33.8%, and non-smokers were 46.8%; family diabetic history - 41.9% had family history, 48.8% were overweight and 10.6% were obese, 55.6 % had sedentary , 28.8% had active and 15.6% had highly active lifestyle. The different group of OHA used were Sulfonylurea 48.9%, Biguanide 41.3% Meglitinide 6.4% and Thiozolidinedione 3.8%. With each class most frequently used drugs were: (a) Sulfonylurea-Glimipiride in 45 patients Glibenclamide in 26 patients Gliclazide in 31 patients Glipizide in 13 patients. (b) Biguanide--Metformin in 98 patients (c) Meglitinide- Repaginide in 15 patients and (d). Thiozolidinedione--Rosiglitazone in 9 patients. The risk factors related to cardiovascular complication like smoking habit, Body Mass Index and Diabetic associated disease were compared. Combination drugs are more effective in controlling blood glucose than that of monotherapy.